AGAMA DAN FILSAFAT DALAM PERSPEKTIF HARUN NASUTION (STUDI ANALISIS FAKTOR-FAKTOR KEBANGKITAN ISLAM INDONESIA) - Ahmad Taofiq (Institut Dirosat Islamiyah Al-Amien Prenduan, 2018)
The combination of Religion and Philosophy has brought Islam to a glorious period in the history of classical Islamic intellectuals. But it does not escape from the opposition of the theologians who argue that the religion which is the absolute truth derived from god can not unite with the truth of philosophy derived from the results of human effort. The most industrious theologian in opposing the mixture of religion and philosophy is Al-Ghozali who disbelieves the muslim philosophers because of their three ideas of natural qadim, Allah does not know the details of nature and the bodily resurrection of the Hereafter does not exist. This led to a long debate between theologians and philosophers. Ibn Rushd, for example, opposes Al-Ghozali's opinion by saying that Al-Ghozali is mistaken in drawing conclusions on what he understood about the thoughts of earlier Philosophers. Indonesian thinkers such as Harun Nasution not only remain silent in addressing it. He says that the inappropriate use of reason will lead to the backward and slow Islam in Indonesia. This research is focused on Harun Nasution's view of religion and philosophy as well as factors of Islamic intellectual awakening in Indonesia. Therefore, the purpose of this research is to know the three things. The research approach is the library (Library research) which is based on Harun Nasution's ideas contained in some of the books we use as the main source. Whatever the result of this research is that Harun Nasution holds that between religion and philosophy there is no contradiction, even go hand in hand and support each other. This is evident in the process of decline wah yu that occurred because of communication between God which he calls the